Supply chain disruption models: A critical review - Niels Bugert; Rainer Lasch (Logistics Research, 2018)
Enterprises affected by supply chain disruptions have reported adverse consequences and dramatic financial losses. Within the research area of supply chain risk management, researchers use simulation models and algorithms to analyze disruption risks and their potential effects on the supply chain. Supply chain disruption risk models focus on ways to quantify and assess disruption risks, study interdependencies between them, and explore the dynamic behavior of risks as they propagate through the network. So far, no review has covered and evaluated quantitative decision models which focus on these specific network-related risk characteristics. This paper derives a definition for supply chain disruption risk odels and analyzes existing approaches on the basis of requirements derived from the literature. Its aims are to structure existing approaches, reveal their shortcomings, and guide future research efforts to improve prospective models systematically. This analysis reveals potential improvements regarding the simultaneous integration of dynamic and interdependent aspects of disruption risks in the supply chain model as well as their propagation through the network. More process steps of a supply chain risk management framework should be supported and more mitigation strategies should be incorporated to expand the scope and usefulness of the models.
Keywords: 650; supply chain disruption; supply chain risk management; simulation; risk management; risk analysis; modeling